2020
DOI: 10.1523/jneurosci.2370-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Interneuron Desynchronization Precedes Seizures in a Mouse Model of Dravet Syndrome

Abstract: Recurrent seizures, which define epilepsy, are transient abnormalities in the electrical activity of the brain. The mechanistic basis of seizure initiation, and the contribution of defined neuronal subtypes to seizure pathophysiology, remains poorly understood. We performedin vivotwo-photon calcium imaging in neocortex during temperature-induced seizures in male and female Dravet syndrome (Scn1a+/−) mice, a neurodevelopmental disorder with prominent temperature-sensitive epilepsy. Mean activity of both putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
58
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 71 publications
10
58
1
1
Order By: Relevance
“…Acute brain slices were prepared at postnatal day (P) 21 to 28, and electrophysiological recordings demonstrated that deficits in action potential generation in parvalbumin-expressing fast-spiking GABAergic interneurons (PV-INs)-known to be dysfunctional in Scn1a þ/À mice-were rescued by the Scn1a.dCas9 system. Recent data suggest that PV-INs in Scn1a þ/À mice that survive to P35 or beyond recover normal intrinsic excitability 7 and in vivo 2photon calcium imaging of PV-INs in awake, behaving Scn1a þ/À mice shows that activity during quiet wakefulness and running behavior is similar to wild-type, 8 supporting the conclusion that PV-IN excitability normalizes over time. These data raise the question as to whether increasing Nav1.1 expression exclusively in PV-INs in a chronic phase of Dravet syndrome would actually be efficacious at all, as these neurons seem to have at least partially "fixed themselves."…”
Section: Commentarymentioning
confidence: 81%
“…Acute brain slices were prepared at postnatal day (P) 21 to 28, and electrophysiological recordings demonstrated that deficits in action potential generation in parvalbumin-expressing fast-spiking GABAergic interneurons (PV-INs)-known to be dysfunctional in Scn1a þ/À mice-were rescued by the Scn1a.dCas9 system. Recent data suggest that PV-INs in Scn1a þ/À mice that survive to P35 or beyond recover normal intrinsic excitability 7 and in vivo 2photon calcium imaging of PV-INs in awake, behaving Scn1a þ/À mice shows that activity during quiet wakefulness and running behavior is similar to wild-type, 8 supporting the conclusion that PV-IN excitability normalizes over time. These data raise the question as to whether increasing Nav1.1 expression exclusively in PV-INs in a chronic phase of Dravet syndrome would actually be efficacious at all, as these neurons seem to have at least partially "fixed themselves."…”
Section: Commentarymentioning
confidence: 81%
“…However, naturalistic seizures have been studied using 2P imaging in mouse models of genetic epilepsies including absence seizures 3 and temperature-induced generalized tonic-clonic seizures in Dravet syndrome (Scn1aþ/-mice). 4 Despite these limitations, the highlighted study takes an important step forward both conceptually and methodologically toward greater understanding of seizure mechanisms. Two-photon calcium imaging and other large-scale imaging modalities, particularly when validated by or in combination with electrophysiology and combined with manipulation of activity, promise to be powerful tools for the studying of mechanisms of seizure initiation and propagation.…”
Section: Commentarymentioning
confidence: 99%
“…And of course electrophysiological methods also continue to advance, including optogenetic tagging of neuronal populations to identify specific cell types 1 and novel probes that facilitate recording of on the order of a thousand single units. 2 Recent studies 3 - 6 have used an optical imaging method, 2-photon laser scanning microscopy (2P imaging) combined with use of genetically encoded calcium indicators (2P calcium imaging) to record seizures. This technique uses a high-powered, pulsed infrared laser that facilitates imaging at depth in light scattering environments such as the intact brain.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper by Tran et al used 2P MCI to monitor neural activity in Ex neurons and parvalbumin-positive (PV + ) In neurons leading up to seizures in Scn1a +/− mice, which model the human disease Dravet Syndrome, 6 involving loss of function of the voltage-gated sodium channel Na(v) 1.1. This design is innovative because it places further constraints on the issue by (1) using a mouse genetic model of epilepsy in which the cellular effects of the causative gene variant are relatively well understood, (2) imaging a genetically defined cell population that is known to be vulnerable to Scn1a loss, and (3) taking advantage of the fact that these mice have temperature-dependent seizures.…”
Section: Commentarymentioning
confidence: 99%